FORMULATION AND PHYSICAL EVALUATION OF LEAF GEL PREPARATIONS PEGAGAN (Centella Asiatica) AS ANTI ACNE - Sabiti, Farroh Bintang; Perwitasari, Yusnita Intan (Jurnal Farmasi & Sains Indonesia, 2024)
Currently, many topical anti-acne drugs are circulating in the form of gels and creams, but there are still very few topical anti-acne drugs that contain herbs, as active ingredients or agents that can potentially prevent and treat acne, such as gotu kola (Centella asiatica) with its anti-bacterial properties. The aim of this research is to develop a stable gotu kola gel formulation. The method used is experimental research methodology. Based on the research results, 1 optimum formula was obtained, namely formulas 1 and 2 with colors following the color of the active substance and transparent, having a distinctive, homogeneous odor, pH 4.5-6.5, good spreadability (5-7 cm) and viscosity ( 3,000-50,000 cP).